Impact on short-lived climate forcers (SLCFs) from a realistic land-use change scenario via changes in biogenic emissions. (6th June 2017) - Scott, C. E.; Monks, S. A.; Spracklen, D. V.; Arnold, S. R.; Forster, P. M.; Rap, A.; Carslaw, K. S.; Chipperfield, M. P.; Reddington, C. L. S.; Wilson, C.
Abstract : More than one quarter of natural forests have been cleared by humans to make way for other land-uses, with changes to forest cover projected to continue. The climate impact of land-use change (LUC) is dependent upon the relative strength of several biogeophysical and biogeochemical effects. In addition to affecting the surface albedo and exchanging carbon dioxide (CO2 ) and moisture with the atmosphere, vegetation emits biogenic volatile organic compounds (BVOCs), altering the formation of short-lived climate forcers (SLCFs) including aerosol, ozone (O3 ) and methane (CH4 ). Once emitted, BVOCs are rapidly oxidised by O3, and the hydroxyl (OH) and nitrate (NO3 ) radicals. These oxidation reactions yield secondary organic products which are implicated in the formation and growth of aerosol particles and are estimated to have a negative radiative effect on the climate ( i.e. a cooling). These reactions also deplete OH, increasing the atmospheric lifetime of CH4, and directly affect concentrations of O3 ; the latter two being greenhouse gases which impose a positive radiative effect ( i.e. a warming) on the climate. Our previous work assessing idealised deforestation scenarios found a positive radiative effect due to changes in SLCFs; however, since the radiative effects associated with changes to SLCFs result from a combination of non-linear processes it may not be appropriate to scale radiative effects from complete deforestation scenarios according to the deforestation extent. Here we combine a land-surface model, a chemical transport model, a global aerosol model, and a radiative transfer model to assess the net radiative effect of changes in SLCFs due to historical LUC between the years 1850 and 2000.